The Pursuit of Making Post-Colonial Malay Muslim-Friendly Nurse Uniforms at the Ministry of Health Malaysia (1957-2018): The Experience of the 'Others' - Saidun, Salilah; Akhmetova, Elmira (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
In this article, the authors adopt the post-colonial lens to report on the nursing uniform transformation at the Ministry of Health Malaysia after Malaysia obtained political independence from Britain and the struggle in making the uniform culturally appropriate for Malay Muslim nurses. Being introduced during the colonial rule, the short-sleeved knee-length uniform carried the colonial values contradictory to the local religious and cultural norms of the majority of the population, this becoming one of the factors that led to the paradoxical under representation of the Malays in the nursing profession. In the third decade of the post-independence period, partial accommodation was granted, allowing Malay nurses to wear short-sleeved uniforms with pants and hair covers. Despite the challenges faced by numerous individuals and organizations who advocated for the cause at various levels, Malay Muslim nurses have been permitted to wear long-sleeved uniforms with pants and headscarves since 2001. The case demonstrates the post-independence struggle in the Malaysian nursing sector that became an 'in-between space' where the intersection between two cultures - the colonial modern nursing dress code and the marginalized 'Other' group's clothing norm - occurs, thus creating a new cultural hybrid leading to a new 'Malay Muslim nurse' identity.